1998
DOI: 10.1507/endocrj.45.563
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of Thyroid Transcription Factor-1 Gene Reveals Absence of Mutations in Patients with Thyroid Dysgenesis but Presence of Polymorphisms in the 5' Flanking Region and Intron.

Abstract: Abstract. Congenital hypothyroidism is caused by several mechanisms.The most common cause worldwide is iodine deficiency, but in iodine-sufficient regions thyroid dysgenesis is the most common cause of congenital hypothyroidism.In the present study we analyzed the thyroid transcription factor-1 (TTF-1) gene in patients with congenital hypothyroidism due to thyroid dysgenesis: three patients with athyrosis, five with ectopy, and one with hypoplasia.Genomic DNA was isolated from peripheral leukocytes, and the TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
2
8
0
2
Order By: Relevance
“…In this case, we analyzed the TTF-1 gene. Consistent with the early studies [29,37,38], no mutation or polymorphism in the coding region of TTF-1 was found. It confirmed that mutations in TTF-1 coding region were likely to be an rare event and were not significant in the pathogenesis of thyroid dysgenesis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this case, we analyzed the TTF-1 gene. Consistent with the early studies [29,37,38], no mutation or polymorphism in the coding region of TTF-1 was found. It confirmed that mutations in TTF-1 coding region were likely to be an rare event and were not significant in the pathogenesis of thyroid dysgenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Up to now, most molecular genetic researches on CH have been done in western countries, some have been carried out in Japanese population [6,28,29]. However,TSHR and TTF-1 genes mutations/variants have not been reported in Chinese population.…”
mentioning
confidence: 99%
“…failed to show NKX2-1 mutations in patients with various types of thyroid dysgenesis (7)(8)(9). In contrast, two patients with a large chromosomal deletion spanning the NKX2-1 gene were found to be affected by a variety of symptoms in the CNS, thyroid, and lung (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Авторы пришли к выводу, что NKX2-1-мутации не являются частой причиной врожден-ного гипотиреоза. Тем не менее частота NKX2-1-мутаций может быть выше у пациентов с врожденным гипотире-озом, ассоциированным с неврологической патологией и заболеваниями дыхательных путей [16][17][18][19]. В недавнем европейском исследовании у 2 из 150 детей с врожденным гипотиреозом были обнаружены мутации гена NKX2-1.…”
Section: клиническая характеристика и диагностикаunclassified